Efficiency of the primary health care policy in Brazilian municipalities: an application of the Pearl's Structural Causal Model - Darlan Christiano Kroth; Raquel Rangel de Meirelles Guimarães (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2021)
ABSTRACT Background In recent years, public health policies and their effects on improving health outcomes have been gaining prominence in the economic literature and on the agenda of international organizations. Objective This study aims to evaluate the causal effect of the "Pacto pela Saúde" (Pact for Health) program on health policy performance in terms of a Health Vulnerability Index (HVI) of Brazilian municipalities from 2006 to 2013. The "Pacto pela Saúde" program is the current operational standard of the Brazilian Unified Health System (SUS). One of the main guidelines of this program was to improve health policy governance. Method The effect resulting from efficiency gains of the participation of municipalities in the health policy on the HVI was estimated by the Pearl's Structural Causal Model. Results The results indicate a positive and significant impact of efficiency management on the reduction of health vulnerability in the municipalities. The Pearl's Causal Model and the back-door criterion of causal identification were employed to calculate the effects of the "Pacto pela Saúde" program on the HVI. Conclusion The use of Pearl's method in this study contributed to a more comprehensive analysis of the effects of the "Pacto pela Saúde" program on health outcomes and, therefore, its use in future research on the analysis of public policies is recommended.